Peran Wanita Sahabat Rasulullah dalam Perang Uhud - Muhammad Gilang Ansori (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2021)
Abstract: This paper studied three things, namely (1) Who are the women friends of the Messenger of Allah who participated in the battle of Uhud? (2) What is the process of the Uhud war? (3) What are the roles of women in the battle of Uhud? To answer the above problems the author used historical research methods and applied the role theory according to Bruce J. Biddle and Edwin J. Thomas. From the study it can be concluded that: (1) There were several women friends of the Messenger of Allah who participated in the battle of Uhud. They were Umm Umarah, Shafiyah bint Abdul Muthalib, Hamna bint Jahsy, Aisha bint Abu Bakr, Umm Aiman, Umm Sulaim, Rufaidah al-Ansariyah and Fatimah az-Zahra bint Rasulullah. (2) The process of the Uhud war began with the revenge of the Quraysh unbelievers in Mecca and ended in the defeat of the Muslims of Medina (3) The role of the women in the battle of Uhud was divided into three parts, namely helping in providing water, assisting in medicine and helping with shouldering weapons with the mujahidin. Keywords: The battle of Uhud, women, Rasulullah, gender